Is "Perversion" Obsolete? - Young, Robert M (PINS-Psychology in Society, 2026)
This is not primarily a clinical paper. It is one of a series (which I hope will make a book) on the general theme of rethinking sexuality in psychoanalysis in the light of the demise of the libido theory and the ascendancy of object relations theory. It includes some clinical material at the end but is centred at an intersection between current cultural debate and psychoanalytic theory.